2013
DOI: 10.1186/1472-6955-12-24
|View full text |Cite
|
Sign up to set email alerts
|

Resident and family perceptions of the nurse practitioner role in long term care settings: a qualitative descriptive study

Abstract: BackgroundResearch evidence supports the positive impact on resident outcomes of nurse practitioners (NPs) working in long term care (LTC) homes. There are few studies that report the perceptions of residents and family members about the role of the NP in these settings. The purpose of this study was to explore the perceptions of residents and family members regarding the role of the NP in LTC homes.MethodsThe study applied a qualitative descriptive approach. In-depth individual and focus group interviews were… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(61 citation statements)
references
References 33 publications
2
59
0
Order By: Relevance
“…Key strategies included part‐time positions for NPs in LTC, weekly meetings with physicians and nurse managers and an office for the NP near the healthcare team to facilitate communication with team members and improve NP integration. Consistent with a previous study (Ploeg et al., ), NPs facilitated family involvement and resident care was timelier. Healthcare teams noted improvements in the quality of nursing documentation as a result of close monitoring of residents by the NPs.…”
Section: Discussionsupporting
confidence: 87%
“…Key strategies included part‐time positions for NPs in LTC, weekly meetings with physicians and nurse managers and an office for the NP near the healthcare team to facilitate communication with team members and improve NP integration. Consistent with a previous study (Ploeg et al., ), NPs facilitated family involvement and resident care was timelier. Healthcare teams noted improvements in the quality of nursing documentation as a result of close monitoring of residents by the NPs.…”
Section: Discussionsupporting
confidence: 87%
“…The relationship with the primary health provider was reported as having the greatest significance to patient satisfaction with respect and trust reported as significant factors. [10][11][12] Several studies in Australia, United Kingdom, United States and Canada [13][14][15][16][17][18][19] reported that patients are satisfied with the care received from NPs. The authors cite satisfaction related to NP communication increased especially when education was provided on disease prevention, health promotion and chronic disease management.…”
Section: Literature Reviewsmentioning
confidence: 99%
“…Nor was the point of view of residents and their families assessed in this project. A more in-depth examination of their views is needed to guide the implementation of NPs in LTC in QuĂ©bec, as researchers in other jurisdictions have found that residents and families appreciated the addition of NPs to LTC teams [85].…”
Section: Discussionmentioning
confidence: 99%